Bioproduction of trans‐Aconitic Acid from Citric Acid by Whole‐Cell Reaction of Escherichia coli Heterologously Expressing the Aconitate Isomerase Gene from Pseudomonas sp. WU‐0701. Issue 7 (25th May 2016) - Kobayashi, Keiichi; Maruebi, Junya; Kirimura, Kohtaro
Abstract: Aconitate isomerase (AI; EC 5.3.3.7) catalyzes the isomerization of cis‐ aconitic acid and trans‐ aconitic acid. Since trans‐ aconitic acid is an unsaturated organic acid, effective and environmentally benign processes are needed for trans‐ aconitic acid production. Here, the genes encoding AI from Pseudomonas sp. WU‐0701 and aconitate hydratase (AH; EC 4.2.1.3) from Escherichia coli W3110, catalyzing the dehydration of citric acid and formation of cis‐ aconitic acid, were co‐expressed in E. coli Rosetta 2(DE3). The recombinant E. coli cells were used as biocatalysts for trans‐ aconitic acid production from citric acid by whole‐cell reaction. The optimal conditions were 37°C and pH 7.0. Using recombinant E. coli cells as biocatalysts for the whole‐cell reaction, 91 mM trans‐ aconitic acid was produced from 400 mM citric acid within 120 min. This is the first report describing a solvent‐ and harmful reagent‐free system for trans ‐aconitic acid bioproduction usable under moderate conditions. Abstract : The recombinant Escherichia coli cells co‐expressing aconitate isomerase and aconitate hydratase genes were used as biocatalysts for trans ‐aconitic acid (tAA) production from citric acid by whole‐cell reaction (see figure). By the whole‐cell reaction of the recombinant E. coli cells, 91 mM tAA was produced from 400 mM citric acid within 120 min. This is the first report describing a solvent‐ and harmful reagent‐free system for tAA bioproduction usable under moderate conditions.